Health promotion through Reproductive Organ Self-Examination (ROSE) training to improve early detection of cervical cancer among women of childbearing age - Elfrida Simamora; Lina Herida Pinem; Joni Siahaan (Bakti Nusantara Pengabdian Masyarakat Indonesia, 2026)
Background: Cervical cancer remains a paramount health issue globally. Early detection is an effective measure to prevent delays in managing cervical cancer. Training of ROSE is expected to assist women in identifying abnormal conditions, as suspected abnormal vaginal discharge with an unpleasant odour can be an early sign of cervical malignancy development. Objective: To improve knowledge and preventive behaviours regarding cervical cancer through reproductive organ self-examination and early detection of cervical cancer using visual inspection with acetic acid. Methods: ROSE was implemented through health education and skills training. A total of 20 female participants of childbearing age took part in this programme at the community health centre. The intervention provided consisted of education related to cervical cancer and training on ROSE using leaflets, power point, modules, and knowledge assessment tools. The questionnaire used to evaluate knowledge comprised 10 items. Results: Based on participant characteristics, 45% of the participants were aged over 41 years, 80% had a senior high school education, 85% were housewives, and 70% did not use contraception. Regarding knowledge levels before and after the training on the reproductive organ self-examination method, the pre-test results showed 25% in the fair category and 75% in the good category. Meanwhile, the post-test results revealed that 100% of the female respondents of childbearing age achieved the good knowledge category. Conclusion: The knowledge of women of childbearing age at the community health centre regarding cervical cancer prevention increased following the training on ROSE method. Furthermore, health behaviours for undergoing early detection of cervical cancer through visual inspection with acetic acid also improved.